Khalida Hussain’s Masroof Aurat (Busy woman): Gender and social analysis - Dr Ambreen Salahuddin (Zaban-o-Adab, 2025)
This article explores the character of busy women in Khalida Hussain’s short story “Masroof Aurat” (Busy Woman). Khalida Hussain is one of the most prominent names of Urdu fiction. She is known for her symbolic style of writing. Her short story “Masroof aurat” (Busy woman) is included in her short story collection “Masroof aurat” (Busy woman), published in 1989. In this first-person account, a woman depicts how she wears different masks and adopting a certain persona, performs tasks accordingly throughout the day. But for her original self, her real identity, she has no persona, as it requires the whole being. The theoretical lenses of Jung’s concept of Persona and Judith Butler’s theory of performativity are used in analysis of this archetype. The concept in Khalida Hussain’s short story is directly adopted from Jung’s persona as it states that every person presents a persona to the world instead of their real self. Butler’s concept states that gender is what we perform. It also aligns with Khalida Hussain’s concept of wearing a relevant mask and performing a task, and in that particular time, becoming the persona that is required and forget about all other masks. In this repeated exercise, the real self is eventually forgotten.